Komunikasi Efektif dalam Berdakwah (Kajian Penggunaan Ejaan Bahasa Indonesia [EBI]) - Arman, Lidya (AL MUNIR : Jurnal Komunikasi dan Penyiaran Islam, 2018)
Da’wah activities cannot be separated from the role of language. Da'wah is a process of delivering messages or information to others by using language as a means of delivering it. Many da'wah messages do not reach the public because of the failure to use the language in delivering it. The language used is not communicative so the message to be conveyed is not well understood by the audience. Because of the failure to use language, the da'wah presented feels dry, arid, and tasteless. Once the importance of language in the development of da'wah, the language used as the means of introduction needs to be considered well. Especially preaching delivered verbally, besides the language factor, there are other things that also play an important role in determining the success of da'wah. It is the speaker or the person who delivered the mission. In connection with the description above, this paper will discuss the following matters; What is the role of language in the development of da'wah.